Characterization of good practices in the elicitation of software requirements referred to in the ISO / IEC / IEEE 29148 standard (Publicaciones en Ciencias y Tecnología, 2021)
The software development process must go beyond the rigorous adoption of a single method or methodology to guide the procedure. It is important to address aspects that threaten the quality of the software, especially failures during the Requirements Engineering (IR) process, specifically in the Requirements Elicitation (ER) stage. A novel way of doing this is work based on good practices, which provides an agile, iterative and lightweight way of working while maintaining what is already done well, while introducing new practices to improve the process. This research aims to identify the good practices of the international quality standard ISO / IEC / IEEE 29148 with an emphasis on the requirements elicitation process. The research is supported by a documentary design research, and the data triangulation research strategy, it was possible to combine the IR with the actions of the quality assurance of the process, standardized by ISO / IEC / IEEE 29148, this contribution incorporates quality aspects in the ER stage to improve the quality of the software by adapting to the needs of the clients and may be used by those companies that still do not apply any method, model or quality standard, as well as those that wish to use international standards in its software development process combining alternatives that allow its rapid and possible adoption.
Keywords: elicitation; ISO / IEC / IEEE 29148; software quality; good practices